Business Strategy Initiative For Sport-Based Entrepreneurship In Yogyakarta Using SWOT-IFE-EFE And TOWS Analysis Case Study: Jogjarenang International Swimming School - Putri Vaerina Lase; Dermawan Wibisono (UNIVED Press, 2025)
Swimming at an early age boosts children's physical and motor skills, builds confidence, and ensures safety around water. High parental awareness and enthusiasm, along with a lack of structured swimming programs in elementary schools, have led to a rise in swimming schools, presenting a significant business opportunity. Jogjarenang International Swimming School, established in 2020 in Yogyakarta City, offers specialized swimming programs for children using the Swim School International (SSI) curriculum. With increasing competition from new schools, Jogjarenang needs a strategic plan to stay competitive. This research uses a mixed-method approach, combining qualitative observations and interviews with quantitative surveys. The SWOT analysis highlights Jogjarenang’s strengths, such as experienced instructors and a strong reputation, but also reveals weaknesses like limited physical resources and instructor shortages. Opportunities include growing swimming awareness and supportive regulations, while threats come from rising competition. The TOWS analysis led to 15 strategic alternatives, with four prioritized strategies in the W-O matrix being recommended.